'The most common form of child mortality in Australia': a human rights analysis of Australia's response to stillbirth in light of the Senate Select Committee Report on Stillbirth Research and Education. Issue 3 (2nd September 2019) - Mowbray, Jacqueline
ABSTRACT: Stillbirth is the most common form of child mortality in Australia, but it has been largely neglected as a public health issue. The Senate Select Committee on Stillbirth Research and Education's Report (the Report), released in December 2018, and the Australian Government's Response, released in July 2019, have raised important questions about Australia's approach to addressing the issue of stillbirth. This article considers that approach in the context of Australia's health-related obligations under international human rights law, especially its obligation under Art. 12(2)(a) of the International Covenant on Economic, Social and Cultural Rights to take steps to reduce its stillbirth rate. This analysis highlights a number of areas in which Australia is failing to meet these international obligations and suggests specific priorities for the Government as it attempts to respond to the challenges that the Report identifies. The article also considers whether, by taking a rights-based approach, the Government could respond more effectively to those challenges and to the tragedy of stillbirth generally.